Comparative Analysis of Topiramate with Amitriptyline in Prophylaxis of Migraine without Aura Among Outpatients Visiting Tertiary Care Hospital - Wahaj Ul Hassan Khan; Ummarah Zafar Farid; Huma Hameed; Umer Naseer; Atifa Gilani; Kamran Ali (Pakistan Armed Forces Medical Journal, 2023)
Objective: To ascertain the better drug between Topiramate and Amitriptyline for the prevention of migraines without aura among patients of the adult age group visiting the tertiary care hospital.